Improved quasi-static twin-fiber transverse compression of several high-performance fibers. Issue 9 (May 2019) - Guo, Zherui; Chen, Weinong; Zheng, James
The method of determining the quasi-static transverse compressive response of several high-performance polymer fibers was improved upon from a previous twin-fiber transverse compression setup in order to detect small initial high compliance signals while maintaining consistent diametral compression. Two fibers were laid parallel between two polished tool steel platens, and the fibers were subsequently compressed using a piezo-electric actuator at quasi-static rates. The new experimental setup ensures that the compression cycle begins when extremely small load signals are detected so that initial elastic transverse moduli may be more accurately measured. Nominal stress–strain curves were obtained for several types of high-performance fibers. The results show good agreement with previously obtained measurements. S-glass fibers exhibited a vastly different mechanical response compared to the polymer fibers.